2005
DOI: 10.1038/sj.leu.2403703
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of methotrexate and methotrexate polyglutamates in lymphoblasts and treatment outcome in children with B-progenitor-cell acute lymphoblastic leukemia: a Pediatric Oncology Group study

Abstract: We reported that children with B-progenitor-cell acute lymphoblastic leukemia (BpALL) treated in the early 1980s whose lymphoblasts accumulated high levels of methotrexate (MTX) and of methotrexate polyglutamates (MTXPGs) in vitro had an improved 5-year event-free survival (EFS) (65% (standard error (s.e.) 12%) vs 22% (s.e. 9%)). We repeated this study in children with BpALL treated in the early 1990s. The major change in treatment was the addition of 12 24-h infusions of 1 g/M 2 MTX with leucovorin rescue (ID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 25 publications
0
52
0
3
Order By: Relevance
“…56 Cellular accumulation of MTX-PGs is recognized as an important determinant of MTX cytotoxicity in ALL lymphoblasts. 12,13,72 Our laboratory and others have previously demonstrated that Bp-ALL cells express 2-to 3-fold higher levels of FPGS mRNA, protein, enzyme activity, and accumulate higher intracellular concentrations of MTX-PGs as compared with T-ALL. 10,14 The ability of cells to accumulate higher intracellular concentrations of MTX-PGs correlates with their in vitro and in vivo sensitivity to MTX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Cellular accumulation of MTX-PGs is recognized as an important determinant of MTX cytotoxicity in ALL lymphoblasts. 12,13,72 Our laboratory and others have previously demonstrated that Bp-ALL cells express 2-to 3-fold higher levels of FPGS mRNA, protein, enzyme activity, and accumulate higher intracellular concentrations of MTX-PGs as compared with T-ALL. 10,14 The ability of cells to accumulate higher intracellular concentrations of MTX-PGs correlates with their in vitro and in vivo sensitivity to MTX.…”
Section: Discussionmentioning
confidence: 99%
“…In childhood ALL a strong correlation exists between FPGS expression, intracellular MTX-PG accumulation and treatment outcome. [10][11][12][13] Our laboratory and others have demonstrated using real-time quantitative reverse transcription-PCR (qRT-PCR), enzymatic activity assays and gene microarrays that FPGS expression (mRNA and enzyme activity) is lineage-specific, with higher level in B-precursor (Bp)-ALL when compared with that in T-lineage (T)-ALL, in both cell line models and clinical samples from patients with ALL. 10,14,15 In normal and malignant lymphohematopoietic cells, the FPGS gene is controlled by at least two mechanisms: one tissue-specific (lineage-specific) and a second proliferation-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…We cannot exclude the possibility that smoking associated mutagens may be toxic to hyperdiploid clones, which have been shown to be especially sensitive to therapeutic chemical agents albeit those associated with poisoning the folate metabolic pathway. 32,33 RAS mutation was more than twice as frequent among Hispanics (28%) compared to non-Hispanic whites (13%). Also, maternal age was clearly associated with incidence of RAS mutation (Tables 1 and 2).…”
Section: 23mentioning
confidence: 99%
“…Thus, it is well known that high-hyperdiploid ALL has a high propensity and that T-cell disease has a low propensity for MTX polyglutamation. [18][19][20][21] High-hyperdiploid ALL is characterized by a median age of 3-4 years and a low white cell count at Leucovorin, methotrexate and relapse risk in childhood ALL TVCh Skärby et al diagnosis, and would thus preferentially be grouped as SR patients, whereas all T-cell patients were classified in the HR/ VHR group. Thus, it is possible that low S-MTX concentration would be most crucial in the SR group, whereas high LV doses would be most deleterious in the HR group.…”
Section: Leucovorin Methotrexate and Relapse Risk In Childhood Allmentioning
confidence: 99%